SOUTH CHINA SEA: THE CHINESE APPROACH (Margalla Papers, 2023)
The international community has shown considerable interest in China's assertiveness in the South China Sea in recent times. The objective of this study is to examine the strengths and weaknesses that form the foundation of Chinese strategies, and decipher the underlying motives and strategies employed by China in its pursuits. The paper evaluates China's current position in the South China Sea and its effects on regional stability and global geopolitics. The findings reveal that China follows a holistic approach with significant infrastructure, diplomatic, and regional geopolitical gains. These efforts expose risks such as regional alliance tensions, international legal framework complexity and though rare but potential armed engagements. Bibliography EntryHussain Awan SI (M), Sajjad. 2023. "South China Sea: The Chinese Approach." Margalla Papers 27 (2): 44-59.